"Sina", "Catayo" or China? The Knowledge of China in the Education of Prince Philip (1527-1556) - Li, Chenguang (Res Publica. Revista de Historia de las Ideas Políticas, 2019)
In the present article, we will emphasize on explaining the knowledge about China that Philip II could acquire through his princely education. We have to remember that Prince Philip lived coinciding with two relevant historical events: the Renaissance and the Age of Discovery. Therefore, in order to train the future king, on one hand, the classical and medieval books were used; on the other hand the new descriptions on previously unknown ranges were adopted. For this reason, we will try to analyze the genetics and the evolution of the names that were used to identify China in these writings: “Sina” in the Classical period, “Catayo” according to the works of the Middle Ages, and “China”, created by the Portuguese in the sixteenth century.
Keywords: Sina; Catayo; China; Education; Felipe II.